Gaps in Breast Reconstruction Patient Educational Resources: Comparing Patient and Surgeon Perspectives - Erica Lee; Lily Zhu; Helen Xun; Chao L. Azad; Pooja Yesantharao; Faraah Bekheet; Justin M. Sacks; Lily R. Mundy; Jennifer Sheng; Kristen P. Broderick (Journal of Reconstructive Microsurgery, 2026)
Abstract Breast reconstruction is an important component of cancer care following mastectomy, improving psychosocial well-being and quality of life. However, not all patients are satisfied with their outcomes. Patient satisfaction with preoperative information is a strong predictor of postoperative satisfaction, but it remains unclear how patient and surgeon perspectives differ regarding the quality and availability of educational resources and which areas of education most need improvement. A cross-sectional survey evaluated patient and plastic surgeon preferences and assessments of breast reconstruction educational resources. Eligible patients were aged 18 years or older and had undergone breast reconstruction. Plastic surgeons were members of the American Council of Educators in Plastic Surgery. Surveys assessed demographics, use of educational resources, and perceived gaps in existing education. The survey was completed by 82 patients and 38 plastic surgeons. Patients most frequently used internet searches (82%), peer support groups (54%), and family and friends (49%) for education outside of clinic visits. Surgeons overestimated patients' use of social media as an educational resource (estimated 50–75%, actual 19%). Both groups identified the feel of the reconstructed breast and the impact on body image as difficult to anticipate preoperatively. Patients reported significantly more difficulty visualizing reconstructive stages (p < 0.01) and skin rippling (p < 0.01), and desired more body image–related education (p < 0.05), realistic images, and reconstruction timelines. Both groups highlighted the need for improved education on breast feel, reconstruction duration and stages, complications, and realistic images. Racial and ethnic minority patients were significantly more likely to desire images reflecting their own skin tone and body type (p < 0.05). Patient and surgeon perceptions of breast reconstruction educational resources are largely concordant but differ in several key areas. Surgeons can enhance patient understanding and satisfaction with reconstruction outcomes by improving visual and representative content and aligning with patient preferences.